跨装置的话音命令 (2019)
本技术的方面涉及一种用于对多个计算装置使用话音命令的方法。从与用户账户相关联的第一计算装置接收第一话音输入数据，其中所述第一话音输入数据包括在所述第一计算装置处捕获的第一话音命令。从与所述用户账户相关联的第二计算装置接收第二话音输入数据，其中所述第二话音输入数据包括在所述第二计算装置处捕获的第二话音命令。基于所获得的第一话音输入数据和第二话音输入数据来确定预期话音命令。基于所述预期话音命令，确定第一目标计算装置。将与所述预期话音命令相关联的第一指令提供给所述第一目标计算装置以供执行。 Aspects of the subject technology relate to a method for using a voice command for multiple computing devices. First voice input data is received from a first computing device associated with a user account, where the first voice input data comprises a first voice command captured at the first computing device. Second voice input data is received from a second computing device associated with the user account where the second voice input data comprises a second voice command captured at the second computing device. An intended voice command is determined based on the obtained first and second voice input data. Based on the intended voice command, a first target computing device is determined. First instructions associated with the intended voice command are provided to